Human dimensions of ecosystem-based management: Lessons in managing trade-offs from the Northern Shrimp Fishery in Northern Peninsula, Newfoundland. (November 2018) - Epstein, Graham; Andrews, Evan; Armitage, Derek; Foley, Paul; Pittman, Jeremy; Brushett, Rebecca
Abstract: Fisheries can have significant impacts on the structure and function of marine ecosystems, including impacts on habitats and non-target species. As a result, management agencies face growing calls to account for the ecosystem impacts of fishing, while navigating the political and economic interests of diverse stakeholders. This paper assesses the impacts of two specific factors on the attitudes and well-being of shrimp fishers in the context of a selective fisheries closure designed to protect crabs in the Northern Peninsula of Newfoundland and Labrador, Canada: (1) the species portfolios of fishers; and (2) democratic rulemaking. The results of this analysis suggest that shrimp fishers were more likely to support selective closures for the shrimp fishery if they also fished for crab, and felt they had an influence on the management of the fishery. The results further indicate that species portfolio diversification had a positive and statistically significant impact on the subjective economic well-being of fishers. This study contributes to an emerging literature on the human dimensions of ecosystem-based fisheries management, highlighting opportunities to address trade-offs in fisheries through species diversification and by enhancing the role and influence of fishers in management processes. Highlights: Many experts highlight the need for policies to address the ecosystem impacts of fishing. Political and economic trade-offs may present challenges for policy change. Selective closures were introduced in Newfoundland to protect crab from shrimp trawlers. Species diversification and political efficacy may enhance prospects for policy change.